2012
DOI: 10.1136/jnnp-2012-303526
|View full text |Cite
|
Sign up to set email alerts
|

Is language impairment more common than executive dysfunction in amyotrophic lateral sclerosis?

Abstract: Background Systematic explorations of language abilities in patients with amyotrophic lateral sclerosis (ALS) are lacking in the context of wider cognitive change. Methodology Neuropsychological assessment data were obtained from 51 patients with ALS and 35 healthy controls matched for age, gender and IQ. Composite scores were derived for the domains of language and executive functioning. Domain impairment was defined as a composite score ≤5th centile relative to the control mean. Cognitive impairment was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
106
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(130 citation statements)
references
References 32 publications
18
106
4
Order By: Relevance
“…A pioneering report of selective action-language deficits in MND [6] was corroborated in subsequent clinical [13][14][15] and neuroimaging [16] studies. Additional imaging evidence obtained from neurotypical samples indicates that the processing of linguistic stimuli related to specific body parts (e.g., the word kick) activates motor contentspecific regions (e.g., cortical areas engaged by leg movement) [17][18][19], but see 20,21].…”
Section: The Emergence Of Motorlanguage Approaches In the Study Of Nementioning
confidence: 90%
“…A pioneering report of selective action-language deficits in MND [6] was corroborated in subsequent clinical [13][14][15] and neuroimaging [16] studies. Additional imaging evidence obtained from neurotypical samples indicates that the processing of linguistic stimuli related to specific body parts (e.g., the word kick) activates motor contentspecific regions (e.g., cortical areas engaged by leg movement) [17][18][19], but see 20,21].…”
Section: The Emergence Of Motorlanguage Approaches In the Study Of Nementioning
confidence: 90%
“…36 A further study demonstrated deficits in syntactic comprehension in 5 of 6 patients who presented with an aphasic syndrome in the context of ALS. 37 Impaired performance on the TROG was reported in 35% of ALS patients in one study, 38 whereas as many as 72% of nondemented ALS patients were reported to be impaired on a Japanese test of syntactic comprehension. 39 Unlike the present study, previous studies have been small, or have not distinguished cases of ALS from those with ALS-FTD.…”
Section: Discussionmentioning
confidence: 99%
“…While traditionally executive dysfunction is regarded as the most common type of cognitive impairment in ALS, high prevalence of language impairment has been Figure 4 Concordance of key C9orf72-specific gray and white matter clusters with reference of healthy controls as identified by various imaging techniques recently established. 24 Our study highlights extensive focal white and gray matter changes in the pars triangularis and pars opercularis regions of the left inferior frontal lobe in association with the C9orf72 ALS genotype (figure e-1). These regions represent the Broca area for most right-handed and the majority of left-handed people.…”
mentioning
confidence: 99%